Plan de marketing para la empresa hostería Las Lagunas ubicada en la parroquia Malacatos del cantón Loja - Vivanco Armijos, Lizbeth Ángeles (2015)
Marketing plan is essential to the operation of any enterprise and the effective and profitable marketing of any product or service, even within the company itself. Planning as a fundamental tool for positioning of a company in the market in which it operates, in this thesis work is proposed as a general objective: "Draw up a Plan of Marketing Plan for the company Hosteria lagoons located in the parish Malacatos, Loja canton", with the aim of improving the service that provides the same. As specific objectives have been raised: "Make an internal diagnosis which will determine us the current situation of the company"; "Make an external diagnosis of the company through the use of the PEST factors"; "Construct the matrix of PORTER's 5 forces to determine providers, substitute services, competition and customers who addressed the service offered; “Run a SWOT analysis for the determination of strategic lines to develop"; "Prioritize the strategic lines according to their importance and individualizing them;" and "Develop the programming budget for each of the defined strategic lines and structures–the". The methodological process used in the development of this thesis required an appropriate selection of methods, techniques and instruments to be used. Among the methods are: the deductive method that allowed us to analyze the gathered information and detect problems in real estate and act in relation to the planning of marketing to the Hosteria "Las Lagunas"; the inductive method was used to learn about particular cases which currently affect the employees and the Manager of the company; the analytical method which used it is in particular to drill down and explore each of the themes and sub-themes explained in the theoretical framework; and the historical method allowed us todetailed data on the evolution of the applicants, i.e. customers of the Hosteria Las Lagunas, which failed to get a sample of the market segment in which our company develops. And techniques used in the development of this work were used: thedirect observation that helped us to determine how the system is and know their operation of the Hosteria Las Lagunas; the interview with the Manager of the Inn the lagoons Mr. Eng. Diego Javier Delgado Bustan company; and polls aimed at the 16 employees that currently the Hosteria Las Lagunas. In addition through random sampling to customers in a total of 376 surveys. Likewise, information was collected for the review of literature, as the frame of reference for all thing related to the Hosteria Las Lagunas, and regarding the conceptual framework everything concerning to the marketing plan. Then presents the results of the information obtained, where there is evidence of the viability of the project since the environment in which it operates the lodge is favorable and presents many opportunities which must be exploited correctly, later in the situational analysis of the company, where it was determined the strategic objectives of the Marketing Plan, such as: develop a plan of advertising and promotions for the "Las Lagunas" lodge in order to improve the image of the same; extend marketing channels, through strategic alliances that will enable it to publicize the services offered by the lodge "Las Lagunas"; make a training plan for employees of Hosteria "Las Lagunas"; design a motivation and incentive plan for employees of Hosteria "Las Lagunas"; and implement the use of uniform newspaper employees who identify them that they are part of the company, which developed jurisdictions.All these strategic objectives have a cost of $13.196,00$. Finally it culminates with the structuring of the respective conclusions and recommendations, which are proposed to the gerente-administrador of Hosteria Las Lagunas implement the Strategic Marketing Plan performed at this thesis, so thus all personnel working in her contribution to growth and development in the market, seeking to achieve proposed strategic objectives, and thus counteract the weaknesses and reduce threats to the company